Solvent exfoliated graphene incorporated mixed phase TiO2 transparent photoelectrode for the efficient and color transparent dye-sensitized solar cell - Shahid, M.U. (Elsevier Ltd, 2020)
Dye-Sensitized Solar Cells have emerged as solar technology for practical application as building-integrated photovoltaic (BIPV) due to low-cost processing, working ability in the ambient environment, and colour transparency. The colour transparency is inherited from the nanostructured mesoporous TiO2 and colourful dye. However, mesoporous TiO2 possesses poor electron transport properties due to multiple grain boundaries, resulting in undesirable recombination reactions that lead to the loss of photoconversion efficiency (PCE). Reduced graphene oxide (rGO) is incorporated in the TiO2 matrix to improve its electron transport properties. Nevertheless, rGO cannot give full benefit of graphene due to its defective structure, which promotes recombination. Therefore, here a solvent exfoliated high-quality graphene in mesoporous TiO2 photoelectrode having mixed phase composition anatase, rutile, and brookite phase is introduced. Graphene/TiO2 hybrid structures are produced with different graphene loading, and their structural, optical, and electron transport properties are thoroughly investigated. Electrochemical impedance spectroscopy (EIS) indicates that electron lifetime increases by 159, electron diffusion length increases by 25, while recombination rate reduces by 62.77 than the pure TiO2 at optimum graphene loading (0.0025 wt). Consequently, an increase of 18.45 and 30.89 PCE is obtained relative to pure TiO2 and commercial paste, respectively. Â© 2020 International Solar Energy Society